STUDY OF THE INHIBITORY EFFECT OF THE ETHANOLIC EXTRACT OF CORIANDRUM SATIVUM, VITIS VINIFERA, AND ZINGIBER OFFICINALE ON THE GROWTH OF STAPHYLOCOCCUS AUREUS ISOLATED FROM MILK OF COWS INFECTED WITH CLINICAL MASTITIS - Massar Ibrahim Shekhan; Jinan Abdul-Amir Sabeeh Al-Hussaini (Basrah Journal of Veterinary Research)
The present study had thrown the light on the in vitro antimicrobial potential of the ethanolic extract of three local medicinal plants; Coriandrum sativum (Coriander), Vitis vinifera (Grape seeds), and Zingiber officinale (Ginger) against the growth of pathogenic Staphylococcus aureus isolated from milk of some local cows infected with clinical mastitis. The antibacterial activity was carried out by using agar well diffusion technique in Mueller-Hinton agar. Four concentrations could be prepared from each plant extract, these concentrations were 50, 100, 200, and 400 mg/ml. The results were obtained by measured the zone of inhibition around the well that could be exhibited by each plant concentration that followed incubation of bacterial plates and expressed as mean±Standard error (SE). Ethanolic extract of Coriandrum sativum was possessed the strongest antibacterial effect among the tested plants, the results were: 29.44±1.17, 29.22±0.32, 27.77±0.99, and 26.11±1.27 mm at a concentration of 50, 100, 200, and 400 mg/ml respectively, Followed by Vitis vinifera extract which showed moderate values recorded as 20.88±0.77, 20.11±0.58, 18.22±0.36, and 20.88±0.35 mm at a concentration of 50, 100, 200, and 400 mg/ml respectively. The least antibacterial activity was exhibited by the extract of Zingiber officinale that produced the following inhibition zones; 15.11±0.80, 15.77±1.12, 17.66±0.33, and 17.55±0.44 mm at a concentration of 50, 100, 200, and 400 mg/ml respectively. On the other hand, S.aureus was variably susceptible to five of the used standard antibiotics; Lomefloxacin, Erythromycin, Amoxicillin, Ciprofloxacin, and Rifampin. Means of their inhibitory zones were; 29.44±0.41, 23.22±0.46, 21.77±0.36, 19.88±0.42, and 11.11±0.26 mm respectively. Whereas Cefprozil showed no effect against the growth of the tested organism.